Synthesis of 4-Oxo-2-Thioxo-3,4-Dihydro-2H, 1,3-Substituted Benzoxazine, Their Transformation with Water, Diazomethane and Amines - M.A. AL-Rawi, Jasim; F. AL-Shahiry, Khalid (Asian Journal of Chemistry, 2010)
The reaction of five mono-substituted salicyloyl chloride with methyl, ethyl and benzylthiocyanate were studied. A mechanism is suggested for the above reaction. Furthermore these products were treated with water, diazomethane, primary and secondary amines. All structures were studied by 1H & 13C nmr and IR-spectroscopy.